Midwives’ perceptions towards the ministry of health guidelines for the provision of immediate postpartum care in rural health facilities in Uganda - Mariam Namutebi; Gorrette K. Nalwadda; Simon Kasasa; Patience A. Muwanguzi; Dan K. Kaye (BMC Pregnancy and Childbirth, 2023)
Abstract Background Guidelines for clinical practice have been part of the Ministry of health’s efforts to improve the quality of care for over two decades. Their benefits have been documented in Uganda. However, having practice guidelines may not always result in their use in care provision. We explored the midwives’ perceptions towards the ministry of health guidelines for providing immediate postpartum care. Methods An exploratory descriptive qualitative study was conducted in three districts in Uganda from September 2020 to January 2021. In-depth interviews with 50 midwives from 35 health centers and 2 hospitals in Mpigi, Butambala, and Gomba districts were done. Thematic analysis of data was done. Results Three themes emerged; awareness and use of the guidelines, perceived drivers, and perceived barriers to the provision of immediate postpartum care. The subthemes for theme I included; awareness of the guidelines, variations in the postpartum care practices, variations in preparedness to manage women with complications, and varied access to continuing midwifery education. Fear of complications and litigation were the perceived drivers of guideline use. On the other hand, lack of knowledge, busy maternity units, organization of the care, and the midwives’ perceptions about their clients were the barriers to guideline use. Midwives felt that new guidelines and policies regarding immediate postpartum care should be disseminated widely. Conclusion The midwives felt that the guidelines were good for the prevention of postpartum complications but their knowledge of the guidelines for the provision of immediate postpartum care was suboptimal. They desired on-job training and mentorship to help them bridge the knowledge gaps. Variations in patient assessment, monitoring, and pre-discharge care were acknowledged and said to be due to a poor reading culture and health facility factors like patient-midwife ratios, unit setup, and prioritization of labor.